Rheological behavor of kaoline water suspensions in presence of surfactants - Сикорский, Алексей Алексеевич; Миронюк, Алексей Владимирович; Свидерский, Валентин Анатольевич (Technology audit and production reserves, 2013)
Despite the great number of works devoted to the rheological behavior of kaolin water suspensions, there are no general guidelines for regulation of coagulation interaction with the addition of an effective concentration of various surfactants to the system, which can be adsorbed on the surface of a mineral. The article presents the study of interaction of kaolin with different surface activity and surfactants of anionic and nonionic types, which is of interest from both scientific and practical point of view, since it will permit to control the viscosity of compositions. It was found that the addition of an anionic surfactant to a suspension reduces the structure strength, and it occurs with a certain concentration. When the concentration is increased or decreased, the structural strength rises again, and in case of a nonionic surfactant, one can observe a monotonic decrease in the stability of structure. In future we will study the effect of stabilization of the modified kaolin suspensions to maximize the content of solid phase in dispersion while maintaining its sedimentation stability during transportation and processing.